Morphology and infraciliature of a new marine ciliate, Cinetochilum ovale n. sp. (Ciliophora: Oligohymenophorea) - Gong, Jun; Song, Weibo (Zootaxa, 2008)
The morphology and infraciliature of a new oligohymenophorean ciliate, Cinetochilum ovale n. sp., isolated from the littoral sediment of the Bohai Sea, northern China, were investigated using live observations and silver impregnations. This new species as follows: size about 20–30 × 15–25 µm in vivo, body oval in outline, with 12–13 bipolar somatic kineties; scutica consisting of two short rows of kinetosomes, positioned near the end of somatic kinety 1; the anterior-most row of its membranelle 1 is distinctly detached from the remaining two rows; three postoral kinetofragments and a cyrtos-like structure at the deep portion of the buccal cavity always present; one macronucleus and one micronucleus; single contractile vacuole terminally located. A key to all known Cinetochilum species is updated.